Flexible Image Sensors with Semiconducting Nanowires for Biomimic Visual Applications. Issue 7 (27th March 2021) - Lou, Zheng; Shen, Guozhen
Abstract : Flexible image sensors with good detectivity, high mechanical stability, and excellent flexibility have generated great interest in biomimetic visual applications. Semiconductor nanowires (NWs) with a unique geometric structure, good transparency, and excellent electronic/optoelectronic properties can cater to flexible applications associated with image sensors. Herein, a comprehensive review of flexible image sensors with semiconducting NWs is offered, and the key performance parameters of photodetectors are introduced in detail. The excellent performances of heterostructure and NW array photodetectors, as well as organic–inorganic hybrid devices, are also reviewed. Finally, new concepts of flexible image sensors, including visual memory, infrared image sensing, and biomimetic electronic eye, are examined to showcase future research in this exciting field. Abstract : Flexible nanowire‐based image sensors with good detectivity, high mechanical stability, and excellent flexibility have aroused great interest in biomimic visual applications. Herein, a comprehensive review of flexible image sensors and its new concepts of biomimic visual application is given.